Pengaruh Model Pembelajaran Kooperatif Tipe TGT (Team Group Tournament) Terhadap Kecerdasan Emosi Siswa MAN 2 Makassar - Muhammad Akbar Syafruddin; Herman Herman (Universitas PGRI Semarang, 2020)
The Effect of TGT (Team Group Tournament) Type Cooperative Learning Model on the Emotional Intelligence of MAN 2 Makassar StudentsThis study aims to examine the effect of the TGT (Team Group Tournament) type of cooperative learning model on the emotional intelligence of MAN 2 Model Makassar students. The population in this study is the total number of MAN 2 Makassar students with a sample of 35 (1 class) randomly selected people, treated using the TGT (Team Group Tournament) type of cooperative learning model. Data on emotional intelligence of students taken using questionnaires. Data were analyzed using the T test with the help of the SPSS 20 application which previously passed the prerequisite test for normal and homogeneity tests. Based on the research results, the following conclusions are made: There is an effect of the TGT (Team Group Tournament) cooperative learning model on students 'emotional intelligence and the TGT (Team Group Tournament) type of cooperative learning model is more effective than conventional learning models in increasing students' emotional intelligence.Keywords: TGT (Team GroupTournament) Type of Cooperative Learning Model, Physical Education, Emotional Intelligence Penelitian ini bertujuan untuk menguji pengaruh model pembelajaran kooperatif tipe TGT (Team Group Tournament) terhadap kecerdasan emosi siswa MAN 2 Model Makassar. Populasi pada penelitian ini adalah jumlah keseluruhan dari siswa MAN 2 Model Makassar dengan sampel berjumlah 35 (1 kelas) orang yang dipilih secara acak, dengan perlakuan menggunakan model pembelajaran kooperatif tipe TGT (Team Group Tournament). Data kecerdasan emosi siswa diambil menggunakan kuisioner. Data dianalisis dengan menggunakan uji T dengan bantuan aplikasi SPSS 20 yang sebelumnya melewati uji prasyarat tes normal dan homogenitas. Berdasarkan hasil penelitian maka dihasilkan kesimpulan sebagai berikut : Terdapat pengaruh model pembelajaran kooperatif tipe TGT (Team Group Tournament) terhadap kecerdasan emosi siswa dan model pembelajaran kooperatif tipe TGT (Team Group Tournament) lebih efektif dibandingkan model pembelajaran konvensional dalam meningkatkan kecerdasan emosi siswa.Kata kunci: Model Pembelajaran Kooperatif Tipe TGT (Team GroupTournament), Pendidikan Jasmani, Kecerdasan Emosi